Factors influencing implementation of health-promoting interventions at workplaces: Protocol for a scoping review. - Kaung Suu Lwin; Aliza K C Bhandari; Phuong The Nguyen; Junko Saito; Akiko Yaguchi-Saito; Erika Ota; Taichi Shimazu (PLoS ONE)
Introduction Health-promoting interventions at workplaces can be effective in modifying lifestyle-related behavioral risk factors for non-communicable diseases (NCDs). However, the interventions are not always successful in the real-world setting, and the evidence for effective strategies to implement the interventions has been limited. We propose a scoping review to identify the topics in need of study and areas for future research on barriers to and facilitators of the implementation of workplace health-promoting interventions. Materials and methods This scoping review will explore these issues from the perspective of supply-side stakeholders, who have a direct role in the implementation of these interventions. An electronic systematic search of MEDLINE (using PubMed), Web of Science, and Scopus databases from 1986 to 2022, in accordance with the PRISMA-ScR guidelines, will be performed. Supplementary hand searching will be undertaken with reference lists from included articles and consulting with relevant stakeholders. Two authors will be responsible for individually screening the corresponding articles by first reading the titles and abstracts and then the full texts to assess whether they meet the inclusion criteria. Data extraction will be conducted using standardized data collection forms, and data analysis will be aligned to the consolidated framework for implementation research (CFIR), a determinant framework of factors affecting implementation, using a directed content analysis approach. Discussion We will present the findings from this review at national and international conferences and submit them to a peer-reviewed journal for publication. Future workplace interventions will significantly benefit from this comprehensive scoping review to identify factors that enable improvement of the implementation, and the barriers to improvement, of evidence-based health-promoting interventions at workplaces.